2008
DOI: 10.1021/cm703500c
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Route to Synthesizing Functionalized Mesoporous SBA-15 Materials with Platelet Morphology and Short Mesochannels

Abstract: A facile synthesis route for preparing SBA-15 silica of platelet shape and very short mesochannels (150-350 nm) was developed by introducing a small amount of Zr(IV) ions in the synthesis solution.The synthesis route can be easily extended to prepare platelet SBA-15 materials with various organic functional groups up to 1.87 mmol/g loading in one pot. In situ XRD and freeze-fracture replication TEM were found to be powerful techniques for studying the self-assembly processes. The platelet SBA-15 with short mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 51 publications
2
91
1
6
Order By: Relevance
“…1-2 lm by adding salts such as KCl and NaCl and keeping the synthesis solution in static condition (Yu et al 2002(Yu et al , 2004Zhao et al 2000). Recently, SBA-15 mesoporous silica with very short mesopore channels in the sub-micrometer scale has also been synthesized (Kosuge et al 2004;Sayari et al 2004;Chen et al 2008Chen et al , 2012Zhang et al 2006;Linton and Alfredsson 2008;Sujandi and Park 2008;Wang et al 2005). These short-channel SBA-15 materials offer significant advantages in the faster rate and the larger capacity for adsorption of bulky molecules, as well as in enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…1-2 lm by adding salts such as KCl and NaCl and keeping the synthesis solution in static condition (Yu et al 2002(Yu et al , 2004Zhao et al 2000). Recently, SBA-15 mesoporous silica with very short mesopore channels in the sub-micrometer scale has also been synthesized (Kosuge et al 2004;Sayari et al 2004;Chen et al 2008Chen et al , 2012Zhang et al 2006;Linton and Alfredsson 2008;Sujandi and Park 2008;Wang et al 2005). These short-channel SBA-15 materials offer significant advantages in the faster rate and the larger capacity for adsorption of bulky molecules, as well as in enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…One is decreasing the particle size of the mesoporous silica to obtain short mesochannels. For example, Zhang et al [7,8] found that submicrometer-sized SBA-15 with highly ordered short pore channels could be prepared in the presence of some alkanes, and Chen et al [15] synthesized SBA-15 with platelet shape and very short mesochannels by adding small amount of zirconium ions to the synthesis mixture. Another way is to introduce secondary large-dimension porosity to the silica materials in addition to the meosporosity generated from the supermolecular templates.…”
Section: Introductionmentioning
confidence: 99%
“…The SC-10 and SC-80 materials are homogeneously dispersed short columns with average pore length of around 450 nm (Fig. 3C-F), a little longer than that of the platelet materials synthesized by Chen et al [13]. The short column morphology is very different from the conventional SBA-15, which possesses rod or fiber morphology (Fig.…”
Section: Xrd and N 2 Adsorption/desorptionmentioning
confidence: 84%
“…As is known, mesoporous SBA-15 with different morphologies, such as fiber, rope, doughnut, sphere, gyroid and discoid, has been synthesized via different approaches [12]. Recently, a facile synthesis route for preparing SBA-15 type material with novel platelet mesostructure (pore length <350 nm) by introducing a small amount of Zr(IV) ions in the synthesis solution was reported by Cheng et al [13]. These materials may be superior to the conventional SBA-15 in facilitating molecular diffusion and less possibility of pore blockage, especially in the reactions of bulky molecules.…”
Section: Introductionmentioning
confidence: 99%